New composite coagulant from agro-waste (tapioca peel) and polyaluminium chloride for primary landfill leachate treatment - Mohd Salleh, Siti Nor Aishah (2021)
Coagulation-flocculation is one of the applications that work efficiently for stabilised leachate treatment, alongside the utilisation of chemical coagulants. On the contrary, the use of chemical coagulants has certain drawbacks towards the health of the ecosystem and living organisms. Hence, this leads to the application of natural material (tapioca peel powder (TPP)) originated and recycled from agro-waste in this study. The limited ability of TPP as a single coagulant could be overcome by substituting the material into polyaluminium chloride (PAC) as a composite coagulant (PACTPP) with different weight ratios. PACTPP was tested on stabilised leachate taken from Simpang Renggam's landfill site (SRLS) by investigating the removal percentage of respective parameters. Based on the weight ratio optimisation, TPP/Al = 3.71 or PACTPPg was determined as the optimum composite coagulant. It was characterised that PACTPPg had combined the best benefits from PAC and TPP, with an acidic property of pH 3.45, a low charge density of 3.45 mV, a higher molecular weight of 1.59 × 107 g/mol, and a bigger particle size of 4.528 × 104 d.mn. By using scanning electron microscopy/energy-dispersive X-ray (SEM-EDX), a longer connected and compact structure was observed with a diameter of 142.3 μm, i.e., 70.1% increment from PAC. Through Fourier-transform infrared (FTIR) and X-ray diffraction (XRD) analyses, PACTPPg was identified to comprise new chemical compounds: the functional groups of ketones, aldehydes, and alkanes in a semi-formed crystalline phase. The newly formed compounds could be associated with the bridging function that becomes the predominant mechanism for PACTPPg’s coagulation behaviour in removing pollutants. Response surface methodology (RSM) was applied after using the conventional method of one-factor-at-a-time (OFAT) optimisation to find the optimum pH for the leachate sample and dosage of PACTPPg. At the optimum conditions of pH 7.13 and 2,446.18 mg/L (479.49 mg/L of Al content), the responses were 59.4% for chemical oxygen demand (COD), 23.7% for ammonia nitrogen, 91.8% for turbidity, 88.5% for colour, and 96.0% for suspended solids of removal percentages. The optimisation also revealed that the performance of PACTPPg was at par with that of PAC+TPP, PAC, and TPP coagulants, especially on the removal of physical parameters. The dosages of PACTPPg were reduced by 33.0% and 26.8% compared to the application of PAC and PAC+TPP, respectively. Meanwhile, from the flocs and sludge formation analyses, PACTPPg worked well for the treatment of landfill leachate by inducing adsorption and bridging between particles > charge neutralisation > sweep flocculation mechanisms with denser generated sludge. PAC+TPP, PAC, and TPP also underwent these kinds of mechanisms but with different superiority, which was portrayed by its percentages of parameter removal. Based on the study, it can be concluded that PACTPPg has the potential to be a sustainable coagulant for the primary treatment of stabilised raw leachate in Malaysia.